CLINICAL COURSE OF MYOCARDITIS IN INFECTIOUS MONONUCLEOSIS IN ADULTS - Shustval, M. F.; Lyadova, T .I.; Volobueva, O. V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2015)
In conducting of complex examination (clinical, laboratory, virological, instrumental) of 186 patients with infectious mononucleosis acute myocarditis was diagnosed in 50 (26,9 %) cases. In 10 % of patients myocarditis was asymptomatic but the clinical picture was veiled by primary infectious process. Drug treatment of viral myocarditis of infectious mononucleosis must include antiviral drugs (acyclovir), drugs that affect the inflammatory, autoimmune and allergic processes, restoration and maintenance of hemodynamic, metabolic drugs, symptomatic therapy.